Long Term Optical Spectroscopy of HD86161 (WR 16) - Niemelä, Virpi Sinikka (2001)
We present results of optical spectroscopy of the emission line star HD 86161=WR 16, the central star of an ejecta ring nebula, obtained between 1971 and 2000 in the wavelength domain 3200-7300 Á. The spectrum of type WN8 is rich in He and N lines, in particular Hell 5-n series emission lines are observed up to high quantum numbers. We analyze possible radial velocity variations observed between different epochs, and find stochastic variations with possible superimposed epoch to epoch variations. These last variations could be due to the orbital motion of an eccentric long period binary system.